Pakistan Development Update, November 2016 : Making Growth Matter - World Bank (World Bank, Washington, DC, 2016)
Pakistan’s growth accelerated in FY16, driven by consumption while investment remained low. Exports continued to fall when soft global demand exacerbated the effects of Pakistan’s long-term decline in competitiveness. After achieving macroeconomic stability, the government continued to deliver on its structural reform agenda in FY16, but much remains to be done if growth is to bestrengthened and sustained. The report begins with a chapter on economic developments, withsections on growth, fiscal policy, the external sector and monetary developments. The second chapter provides an outlook and describes upcoming challenges, including structural reform needs and progress in social indicators. The final chapter identifies several topical issues for detailed analysis, including sections on poverty, nutrition, Karachi urban planning and infrastructure, and the FY17 federal budget.